Retrospective analysis of the effects of radiotherapy on the areolas reconstructed with a total skin graft - Marcela Caetano Cammarota; Anderson de Azevedo Damasio; Suellen Vieira da Silva; Rafael Sabino Caetano Costa; Carolina Oliveira Paranagua Castro; Tristão Maurício de Aquino; Phabio Claudino Estrela Terra Theodoro; José Carlos Daher (Revista Brasileira de Cirurgia Plástica, 2021)
Introduction: Breast cancer has increased progressively in recent years, and with this, the need for diagnosis and earlier treatment has also increased. Currently, in Brazil, breast cancer accounts for 29.7% of cancer cases in women. The reconstruction of the nipple-areolar complex (NAC) has focused on greater attention due to the search for symmetry and naturalness, which is the final stage of this whole process. The objective is to evaluate the maintenance of the size, contour, color, symmetry and shape change of reconstructed NAC after mastectomies associated with radiotherapy. Methods: A retrospective study was conducted analyzing the evolution of reconstructed areolas after total mastectomy associated with adjuvant treatment with radiotherapy. Two groups were selected: group 1 (unilateral reconstruction) and group 2 (bilateral reconstruction). Comparisons were made between the reconstructed NAC areola, group 1, with that of the contralateral NAC and in group 2, between the two reconstructed areolas Results: After the inclusion of 56 patients in the study, 71 reconstructed areolar complexes were included. Symmetry was classified as good in 77.46% of all cases (p=0.706). Twenty-five reconstructions were performed in areas under the effect of radiotherapy, and only 9 cases showed decreased areola size (p=0.050), evolving with an asymmetry in 8 cases, 4 in the radiotherapy region (p=0.706). The areolar contour showed a similarity between cases treated with radiotherapy and untreated (p=0.918). Conclusion: Adjuvant radiotherapy was a predisposing factor for changes that may arise during the postoperative period of reconstruction of the nipple-areolar complex, according to statistical analysis.